A vulnerabilidade externa brasileira no regime cambial de flutuaç\~ao suja - Saulo Quadros Santiago (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This paper analyzes Brazilian vulnerability to changes in international state of expectations as a result from the nature of its insertion in the external scenario and from institutional changes in foreign exchange market and financial account convertibility. For that purpose, it evaluates the capacity of obtaining current revenues in foreign currency, the behavior of foreign financial flow towards domestic economy and the positions in external assets and liabilities. From empirical data, it is verified that current revenues in foreign currency has been spurious, that external financial flow has been volatile, oscillating according to the state of international expectations, and that net external liabilities presented growth along in the 2000's. Moreover, this paper shows that exchange reserves are insufficient to meet both external commitments and liquidation of foreign portfolio investment in local markets, in a situation of state of expectations deterioration.
Keywords: F32; F44; 330; external vulnerability; floating exchange rate; capital flows; external competitivity